1994
DOI: 10.1073/pnas.91.26.12619
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic binding of the Vibrio fischeri LuxR transcriptional activator domain and RNA polymerase to the lux promoter region.

Abstract: LuxR, the Vibno fischeri luminescence gene (lux) activator, is the best-studied member ofa family of bacterial transcription factors required for cell density-dependent expression of specific genes involved in associations with eukaryotic hosts. Neither LuxR nor any other LuxR homolog has been shown to bind DNA directly. We have purified the LuxR C-terminal transcriptional activator domain from extracts of recombinant Escherichia coli in which this polypeptide was expressed. The purified polypeptide by itself … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
173
0
3

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(182 citation statements)
references
References 37 publications
6
173
0
3
Order By: Relevance
“…Perhaps the lower average and larger error bars is due to stochastic binding of 3OC6 and the resulting inconsistent forward vs. backward transcription from the same promoter. The literature indicates that LuxR binds Plux only after 3OC6 binds to LuxR 14,15,[24][25][26] . Our results show that the BioBrick part containing Plux supports backwards transcription when LuxR is present in the cell and 3OC6 is absent.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Perhaps the lower average and larger error bars is due to stochastic binding of 3OC6 and the resulting inconsistent forward vs. backward transcription from the same promoter. The literature indicates that LuxR binds Plux only after 3OC6 binds to LuxR 14,15,[24][25][26] . Our results show that the BioBrick part containing Plux supports backwards transcription when LuxR is present in the cell and 3OC6 is absent.…”
Section: Resultsmentioning
confidence: 99%
“…Our results indicated that the Plux promoter is bidirectional and is induced "backwards" by LuxR in the absence of 3OC6. The backwards transcription in the absence of 3OC6 had not been documented in the literature 14,15,[24][25][26] . In the V. fischeri genome, the Plux promoter points in the direction of the LuxI gene and away from the LuxR gene.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, LuxI is a synthase that catalyzes a reaction between S-adenosyl methionine and an acyl carrier protein to produce an acyl-homoserine lactone (AHL) that freely diffuses out of the bacterial cell [7]. At high concentrations, the AHL will diffuse back into the cell and bind to its cognate cytoplasmic receptor LuxR and induce the transcription of the luciferase operon, forming an autoregulatory feedback loop (Figure 1) [8][9][10][11][12]. Since this first description, numerous LuxI/LuxR homologous systems have been identified in more than a 100 Gram-negative bacteria and have been shown to regulate a variety of genes involved in a plethora of functions including virulence gene expression, motility, biosynthesis of bacteriocins and biofilm formation [1,3,13].…”
mentioning
confidence: 99%
“…As more AI is produced, their concentration starts to increase outside the cell, diffusing back into the cell and binding more frequently to LuxR, forming a stable complex. This complex will then activate the luxICDABE operon that codes for luciferase (Stevens et al, 1994). Without the AHL, LuxR is very unstable and gets degraded, and only with a high concentration of the autoinducer can the stable AHL-LuxR complex be formed.…”
Section: Quorum Sensing In Aliivibrio Fischerimentioning
confidence: 99%